2023
DOI: 10.1002/ejsp.2987
|View full text |Cite
|
Sign up to set email alerts
|

The impact of education about historical and current injustices, individual racism and systemic racism on anti‐Indigenous racism

Iloradanon H. Efimoff,
Katherine B. Starzyk

Abstract: Anti‐Indigenous racism is a pressing issue in Canada. Education on historical and contemporary Indigenous topics is a common strategy to challenge such racism. Despite the existence of education‐based programmes intended to address anti‐Indigenous racism, there is limited evidence that they are effective. To this end, we report the results of two longitudinal experiments (N1 = 639, N2 = 1099) assessing the effect of education on anti‐Indigenous racism. In both studies, we assessed the impact of five conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…One possible reason is that the mode of delivery did not matter as much as the content of critical historical knowledge. Gaining such an understanding certainly has many prosocial consequences for how people think, feel, and behave toward outgroup members (Hill and Augoustinos, 2001;Adams et al, 2008;Nelson et al, 2012;Salter and Adams, 2016;Bonam et al, 2019;Neufeld et al, 2021;Zell and Lesick, 2022;Efimoff and Starzyk, 2023). Another possibility is that the school was not maximally immersive.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…One possible reason is that the mode of delivery did not matter as much as the content of critical historical knowledge. Gaining such an understanding certainly has many prosocial consequences for how people think, feel, and behave toward outgroup members (Hill and Augoustinos, 2001;Adams et al, 2008;Nelson et al, 2012;Salter and Adams, 2016;Bonam et al, 2019;Neufeld et al, 2021;Zell and Lesick, 2022;Efimoff and Starzyk, 2023). Another possibility is that the school was not maximally immersive.…”
Section: Discussionmentioning
confidence: 99%
“…As well, Neufeld et al (2021), who either measured or manipulated critical historical knowledge (via the length or processing of a written passage) in five studies, found non-Indigenous participants who knew more reported empathy toward Indigenous people and were more likely to believe that residential schools continue to cause harm. Finally, in two experimental longitudinal studies, Efimoff and Starzyk (2023) found brief critical historical knowledge videos positively improved non-Indigenous participants' knowledge, attitudes, feelings, and behaviors toward Indigenous people.…”
Section: Critical Historical Educationmentioning
confidence: 92%
See 3 more Smart Citations